1982
DOI: 10.1055/s-0038-1657144
|View full text |Cite
|
Sign up to set email alerts
|

DDAVP Stimulates Prostacyclin Production

Abstract: SummaryDes-amino-D-arginine vasopressin (DDAVP) stimulates the release of factor VIII and plasminogen activator from the vascular endothelium. An infusion of exogenous factor VIII given to haemophiliacs causes an increase in platelet activation. This activation does not occur after stimulating a rise in the patient's own factor VIII level caused by DDAVP infusion. We hypothesised therefore that DDAVP could also cause the endothelial release of prostacyclin (PGI2), a potent anti-platelet agent which would count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

1984
1984
1993
1993

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 3 publications
3
12
1
Order By: Relevance
“…These results confirm our previous find ings [7] that DDAVP stimulates PGI2 pro duction in normal and haemophilic patients. This finding has been questioned by D'An gelo et al [15] who could find no effect of DDAVP on PGI2 production, but this may have been due to differences in the method ology [16].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results confirm our previous find ings [7] that DDAVP stimulates PGI2 pro duction in normal and haemophilic patients. This finding has been questioned by D'An gelo et al [15] who could find no effect of DDAVP on PGI2 production, but this may have been due to differences in the method ology [16].…”
Section: Discussionsupporting
confidence: 93%
“…The mechanism for the action of DDAVP on PGI2 production is not en tirely clear. Previous in vitro studies have shown DDAVP to have a direct stimulatory effect on PGI2 production from arterial tissue [7], while there is mounting evidence that the effect of DDAVP on FVIIR:Ag release is mediated via a secondary messenger [20,21]. In the absence of any change in TxB2 levels following DDAVP, the stimulatory effect on PGI2 production may be mediated through an endothelial cell receptor rather than a gen eral activation of the arachidonic acid cas cade.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Since anephric patients respond normally to DDAVP (Mannucci et al, 1975), the site of the V, receptors involved in the hemostatic properties of DDAVP is not in the kidney. DDAVP is without effect on platelets (Yang et al, 1990;Belch et al, 1982;D'Angelo et al, 1983). However, platelets possess V,- (Pollock and MacIntyre, 1986) but not V,-receptors (Seiss et al, 1986;Yang et al, 1990) and DDAVP is a specific V2-receptor agonist (Jard, 1988).…”
Section: Discussionmentioning
confidence: 99%